Integrating Tradition and Modernity in Islamic Higher Education: a Phenomenological Study of the Boarding System - Slamet Riyadi; Muhammad Ridha; Mowafg Abrahem Masuwd; Naser Ali Abdulghani; Suhendri (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
This study examines the integration of pesantren traditions with modern higher education at STAI As-Sunnah, an Islamic college in Indonesia. Employing a phenomenological approach, the research analyzes how this institution balances traditional values with contemporary educational demands. Key findings highlight STAI As-Sunnah's success in maintaining a focus on Arabic language learning and Islamic values while offering accredited study programs. However, the study also identifies discourses surrounding gender inclusivity, access to technology, and the balance between tradition and modernity. The study concludes that adopting more inclusive and adaptive approaches, such as blended learning, may help STAI As-Sunnah become an innovative model in Islamic higher education, contributing significantly to the development of Islamic education in Indonesia.